Nana oforiatta ayim: “The mobile museum is a project where we learn as much as we bring in” - United Nations Educational, Scientific; Cultural Organization; Anuliina Savolainen (The UNESCO Courier, 2024)
In Ghana, Nana Oforiatta Ayim’s mobile museum brings art to places where everyday life happens, from fishing harbours to market squares. The testimonials and objects shared by the visitors feed into a wider project of mapping the African continent’s cultural landscape, while offering an alternative to the Western museum model. Interview with Nana Oforietta Ayim, Ghanaian writer, cultural historian, curator and filmmaker.